Playing with Fire : Feminist Thought and Activism through Seven Lives in India. - Writers, Sangtin (University of Minnesota Press, 2006)
Playing with Fire is written in the collective voice of women employed by a large NGO as activists in their communities and is based on diaries, interviews, and conversations among them. Together their personal stories reveal larger themes and questions of sexism, casteism, and communalism, and a startling picture emerges of how NGOs both nourish and stifle local struggles for solidarity.